If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -48 + 7x = -12 Reorder the terms: -48 + 5x + 7x = -12 Combine like terms: 5x + 7x = 12x -48 + 12x = -12 Solving -48 + 12x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 12x = -12 + 48 Combine like terms: -48 + 48 = 0 0 + 12x = -12 + 48 12x = -12 + 48 Combine like terms: -12 + 48 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 9m+19m=84 | | 6x-6=0.5x+38 | | 12x-5=30x+1 | | 5x-48+7x=-21 | | 1/7*y=-15 | | 9-72/3 | | (3x^2-13x-10)/(x-5) | | y/7=-15 | | -0.43=0.03x+0.15 | | 2y=10x | | 3.3333333333333333x+20=x+34 | | -5k+123=6k+7 | | 23/4+64/5 | | 23/4+34/5 | | 3*p=-15 | | 45.5a-52=2a-5 | | 0=u^2-54 | | -4z+20=3z+9 | | 51=5x-9 | | 5x+16=7x-14 | | -z+5=3z+9/4 | | (83*.8)+(x*.2)=70 | | 173-6x=30x+17 | | -z+5=(3z+9/4) | | 14-7x=34-14x | | 8x+90+26=180 | | 6x-7=(2x/9)-5 | | 4n+3(-3+5n)=-104 | | 2x+15-9x=7x+(3-6) | | 9.2x^2-24.6=0 | | 9+1/-20=10 | | 4x+7-2x=11+2x |